2020
DOI: 10.1111/bdi.12921
|View full text |Cite
|
Sign up to set email alerts
|

Call to action regarding the vascular‐bipolar link: A report from the Vascular Task Force of the International Society for Bipolar Disorders

Abstract: Objectives The association of bipolar disorder with early and excessive cardiovascular disease was identified over a century ago. Nonetheless, the vascular‐bipolar link remains underrecognized, particularly with regard to how this link can contribute to our understanding of pathogenesis and treatment. Methods An international group of experts completed a selective review of the literature, distilling core themes, identifying limitations and gaps in the literature, and highlighting future directions to bridge t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(53 citation statements)
references
References 262 publications
(294 reference statements)
0
50
0
3
Order By: Relevance
“…Further, in mood disorders there is a heightened prevalence of cooccurring medical conditions such as obesity, diabetes and cardiovascular disease (Coello et al, 2019;Dalack and Roose, 1990;Goldstein et al, 2020;Mansur et al, 2019). These have been linked to a more severe coronavirus 2 (SARS-CoV-2) manifestation (Zaman et al, 2020), and may amplify psychological distress by increasing a patient's worries about the heightened personal risk of infection-related mortality or poor long-term health outcomes (Goldstein, 2017;Mansur et al, 2015;Zaman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Further, in mood disorders there is a heightened prevalence of cooccurring medical conditions such as obesity, diabetes and cardiovascular disease (Coello et al, 2019;Dalack and Roose, 1990;Goldstein et al, 2020;Mansur et al, 2019). These have been linked to a more severe coronavirus 2 (SARS-CoV-2) manifestation (Zaman et al, 2020), and may amplify psychological distress by increasing a patient's worries about the heightened personal risk of infection-related mortality or poor long-term health outcomes (Goldstein, 2017;Mansur et al, 2015;Zaman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Together, the results demonstrate subtle BP differences in BD subjects within a normotensive range and that mean BP is associated with mood instability in a transdiagnostic group. Despite the high prevalence of cardiovascular mortality in BD, a focus on prevention and risk management in BD is regrettably lacking (Goldstein et al 2020). Yet, BP is a highly modifiable risk factor.…”
Section: Resultsmentioning
confidence: 99%
“…We found no evidence of differences in arterial stiffness between cases and controls. Few studies have examined arterial stiffness in bipolar disorder 46 and either found no evidence of differences between cases and controls 31,47 or age-dependent differences that suggested higher arterial stiffness in older patients with bipolar disorder compared to age-based population norms 48 .…”
Section: Discussionmentioning
confidence: 99%